Pengaruh Penerapan Media Wordwall terhadap Motivasi Belajar Bahasa Jepang Siswa SMA Angkasa 2 Jakarta: The Effect of Implementing Wordwall Media on the Japanese Language Learning Motivation of Students at Angkasa 2 Senior High School, Jakarta - Muhammad Nurul Hadi; Frida Philiyanti; Cut Erra Rismorlita (Jurnal Pendidikan Bahasa Jepang Undiksha, 2026)
This research analyzed the implementation and influence of Wordwall on students' Japanese language learning motivation at SMA Angkasa 2 Jakarta. It also aimed to know students' responses regarding the strengths and weaknesses of Wordwall media. Using a one-group pre-test post-test design, a sample of 33 eleventh-grade students was involved. Research instruments included closed and open-ended questionnaires. The paired sample t-test results show a significant increase in motivation scores, from a mean of 58.45 (pre-test) to 63.33 (post-test), with a significance of 0.005. The results of the simple linear regression test with the equation Y = 18.012 + 0.639X and a coefficient of determination (R2) value of 0.241. These results indicate that Ha is accepted and H0 is rejected, which means that the Wordwall media has an effect on the Japanese language learning motivation of students at Angkasa 2 High School in Jakarta with an effect of 24.1%. Qualitatively, students' responses reveal that Wordwall strengths are its enjoyable, diverse game variations, and ability to foster a competitive spirit through its leaderboard feature. Conversely, the main weaknesses include occasional delays or lags and the need for a stable internet connection for optimal use.